Silane-coated magnetic nanoparticles with surface thiol functions for conjugation with gold nanostars. Issue 48 (23rd November 2015) - Pallavicini, Piersandro; Cabrini, Elisa; Casu, Alberto; Dacarro, Giacomo; Antonio Diaz-Fernandez, Yuri; Falqui, Andrea; Milanese, Chiara; Vita, Francesco
Abstract : Superparamagnetic magnetite nanoparticles are coated with a tunable number of free surface –SH, enabling them to decorate gold nanostars. Abstract : Small ( d ∼ 8 nm) magnetite nanoparticles, Fe3 O4 NP, are prepared and coated with mercaptopropyl trimethoxysilane (MPTS) to form Fe3 O4 NP@MPTS. In the coating step controlled MPTS/Fe3 O4 NP molar ratios are used, ranging from 1 to 7.8 × 10 4 . The total quantity of MPTS per Fe3 O4 NP is determined by SEM-EDS analysis and the average number of free, reactive –SH groups per Fe3 O4 NP is calculated by a colorimetric method. At very low molar ratios MPTS forms a submonolayer on the Fe3 O4 NP surface with all –SH free to react, while on increasing the MPTS/Fe3 O4 NP molar ratio the (CH3 O)3 Si– groups of MPTS polymerize, forming a progressively thicker shell, in which only a small fraction of the –SH groups, positioned on the shell surface, is available for further reaction. The MPTS shell reduces the magnetic interactions occurring between the magnetite cores, lowering the occurrence and strength of collective magnetic states, with Fe3 O4 NP@MPTS showing the typical behaviour expected for a sample with a mono-modal size distribution of superparamagnetic nanoparticles. Interaction of Fe3 O4 NP@MPTS with gold nanostars (GNS) was tested, using both Fe3 O4 NP@MPTS with a MPTS submonolayer and with increasing shell thickness. Provided that a good balance is used between the number of available –SH and the overall size of Fe3 O4 NP@MPTS, the free thiols of such nanoparticles bind GNS decorating their surface, as shown by UV-Vis spectroscopy and TEM imaging.